Malignant peritoneal mesothelioma presenting with bilateral hydronephrosis and renal insufficiency: a case report and literature review - Luo, Jisheng; Pan, Jinhong; Zhong, Chuanhua; Wang, Lina; Zhang, Heng (Frontiers in Surgery, 2024)
Introduction: Malignant peritoneal mesothelioma (MPM) is an extremely rare tumor with nonspecific clinical manifestations, challenging to diagnose. Case presentation:Herein, we reported a case of MPM with occult onset presenting with bilateral hydronephrosis and renal insufficiency. A 30-year-old man was admitted to the urology department with recurrent bilateral low back pain. The etiology was unclear after a series of laboratory tests, imaging examinations, bone marrow aspiration, renal puncture biopsy, ascites examination, ureteroscopy, and so on. Finally, MPM was diagnosed by laparoscopic exploration and biopsy. Moreover, during the course of the disease, the patient's bilateral ureters were compressed, and the obstruction could not be relieved after the placement of ordinary ureteral stents. Percutaneous nephrostomy (PCN) or metal ureteral stenosis was appropriate in managing malignant ureteral obstruction as it could improve renal function. Conclusions: The onset of this case was insidious, and the diagnosis was difficult, with a poor prognosis. To date, only a handful of cases have been reported. We hope this case can provide some enlightenment for our clinical work.